Multiplex RT-PCR assay for detection of common fusion transcripts in acute lymphoblastic leukemia and chronic myeloid leukemia cases - Nittaya Limsuwanachot (2018)
Background: Acute lymphoblastic leukemia (ALL) is a heterogeneous disease which requires a risk-stratified approach for appropriate treatment. Specific chromosomal translocations within leukemic blasts are important prognostic factors that allow identification of relevant subgroups. In this study, we developed a multiplex RT-PCR assay for detection of the 4 most frequent translocations in ALL (BCR-ABL, TEL-AML1, MLL-AF4, and E2APBX1). Materials and Methods: A total of 214 diagnosed ALL samples from both adult and pediatric ALL and 14 cases of CML patients (154 bone marrow and 74 peripheral blood samples) were assessed for specific chromosomal translocations by cytogenetic and multiplex RT-PCR assays. Results: The results showed that 46 cases of ALL and CML (20.2%) contained the fusion transcripts. Within the positive ALL patients, the most prevalent cryptic translocation observed was mBCR-ABL (p190) at 8.41%. In addition, other genetic rearrangements detected by the multiplex PCR were 4.21% TEL-AML1 and 2.34% E2A-PBX1, whereas MLL-AF4 exhibited negative results in all tested samples. Moreover, MBCR-ABL was detected in all 14 CML samples. In 16 samples of normal karyotype ALL (n=9), ALL with no cytogentic result (n=4) and CML with no Philadelphia chromosome (n=3), fusion transcripts were detected. Conclusions: Multiplex RT-PCR provides a rapid, simple and highly sensitive method to detect fusion transcripts for prognostic and risk stratification of ALL and CML patients.